ANALISIS USAHATANI DAN PEMASARAN TOMAT DI DESA GUNUNG INTAN KECAMATAN BABULU DARAT KABUPATEN ENAJAM PASER UTARA - Siti Balkis; Muhammad Najib; Elis Siti Masitoh (DINAMIKA PERTANIAN, 2014)
The objective of this research was to determine the cost, revenue, income, and efficiency of tomato farming and analysis marketing tomato product in Gunung Intan Village, Penajam Paser Utaraa Sub District. This research was started on January until March 2014, with research location in Gunung Intan Village, Penajam Paser Utara Sub District. The method that used is census method. A total of 25 tomato farmers was established as respondents. The data collected were primary and secondary data. Primary data were obtained by observation and interview with responded by using questionnaire which was compiled in line with research. The secondary data were come from bibliography study and institution information which is related to research execution. The results showed that the average of production cost of tomato farming per season was Rp. 19,401,805.71 mt-1 or Rp. 49,532,992.06 ha-1 respondent-1. The total revenue was Rp. 55,419,840 mt-1 with an average of farm income was Rp. 36,018,034.29 mt-1 or Rp. 89,250,310.48 ha-1 respondent-1. Value of R/C was 2.84 and it means that the cultivated tomato farm is profitable. The tomato marketing channel in Gunung Intan’s Village was 3 channel levels, i.e., tomato farmer–supplier–merchant–trader–consumer.